Serum S100B Protein Levels in Patients with Panic Disorder: Effect of Treatment with Selective Serotonine Reuptake Inhibitors - Turkcapar, Mehmet Hakan; Kaya, Berna Cagatay; Karadag, Hasan; Oner, Ozgur; Kart, Aysegul (KOREAN NEUROPSYCHIATRIC ASSOC, 2015)
Objective Altered serum S100B protein levels have been shown in several psychiatric disorders. Our aim was to investigate whether plasma S100B is different in patients with panic disorder (PD) when compared with controls. Our second aim was to investigate whether treatment with SSRIs have an effect on S100B levels in patients with PD. Methods The sample included 32 patients diagnosed with PD (21 women, 11 men) per DSM-IV criteria and 21 healthy controls (11 women, 10 men). S100B levels were measured with BioVendor Human S100B ELISA (Enzyme Linked Immunosorbent Assay) kit. Results 14 patients were not on drug treatment (43.8%) while 18 patients were taking various SSRls. Median S100B value was 151.7 pg/mL (minimum-maximum: 120.4-164.7 pg/mL) in the control group, 147.4 pg/mL (minimum-maximum: 138.8-154.1 pg/mL) in the drug free group and 153.0 pg/mL (minimum-maximum: 137.9-164.7 pg/mL) in the treatment group. Kruskal-Wallis analysis showed a significant diffrerence among the three groups (z=9.9, df=2, p=0.007). Follow up Mann-Whitney-U tests indicated that while the control and the patients with treatment were not significantly different (z=-0.05, p=0.96), there were significant differences between the control group and untreated patients (z=-2.6, p=0.009) and treated and untreated patients (z=-3.0, p=0.003). Conclusion Our results suggested that, serum S100B protein level might be decreased in untreated PD patients and that patients who were treated with SSRIs had similar S100B level to healthy controls
Keywords: S100B protein; Panic disorder; Selective serotonine reuptake inhibitors